Treatment of Primary Infected Juxtarenal Aortic Aneurysm With the Multilayer Stent. (October 2013) - Flis, Vojko; Matela, Jože; Breznik, Silva; Kobilica, Nina
Purpose: To report the use of multilayer uncovered stent to treat primary infected juxtarenal aortic aneurysm. Case Report: A 50-year-old man was admitted to hospital for rapid onset of intractable abdominal pain and high fever. Computed tomographic scan showed 2 juxtarenal saccular aneurysms of abdominal aorta with morphologic and clinical changes compatible with infectious etiology. Patient was treated with multilayer flow-modulating stent. Follow-up imaging showed persistent aneurysm exclusion and continuous aneurysm shrinkage of the sac until complete regression to a normal aortic configuration was seen at 1 year. During follow-up (24 months), patient continued to do well, and there was no recurrence of infection. Conclusion: Multilayer stent appeared to be an acceptable treatment option for primary infected juxtarenal aortic aneurysms. Aneurysmal sac completely disappeared and visceral branches remained patent at 2-year follow-up. However, longer follow-up is necessary to evaluate the long-term patency of involved visceral arteries.